In Search of a Professional Identity: An Analysis of Photographic and Illustrative Images of Nurses in Japan. - Honoka Araki; Mizuki Imai; Teresa Elizabeth Stone (Halla Newcastle Education and Research Center, 2022)
Purpose Inaccurate portrayals of nurses and their roles in the media contribute to misleading public stereotypes that negatively affect the status and value of nurses. This study aims to clarify how nurses are portrayed visually on the Internet in Japan and what these images suggest about the role, value, and professional status of nurses in Japan. Methods A descriptive mixed methods study: Forty photographs of nurses and 40 illustrations of nurses were analysed to make judgments about consistency with a contemporary profile that informs guidelines for professional education and practice. Results Over three quarters (77.5%) of the images showed only female nurses and 55% were depicted smiling politely. None of the images depicted nurses engaged in high level care consistent with that of a professional dealing with typical contemporary client/patient needs. Conclusion Our study suggests that in common with overseas research, nurses were predominantly being portrayed as feminine and caring but not as professionals capable of independent practice. Although representations were usually positive, the depictions were not entirely accurate, and this was more evident in the illustrations. Imagery can have a profound effect on ideas, attitudes and behavior; it is imperative that nurses are depicted as appropriately educated professionals and that stereotypes such as nurses being young, subservient, and female should be challenged.